VALUABLE LINGUISTIC EDITION – FIRST LEXICOLOGY OF THE MACEDONIAN LANGUAGE: (Simona Gruevska-Madjoska, Lexicology of Macedonian Language,МI-AN, Skopje 2021, 229 pp.) (Journal of Contemporary Philology, 2022)
(Simona Gruevska-Madjoska, Lexicology of Macedonian Language,МI-AN, Skopje 2021, 229 pp.)
Keywords: Review